Аналіз стану формування професійної компетентності майбутніх слідчих у ЗВО зі специфічними умовами навчання - Скляр, О. С.; Skliar, O. S.; ORCID: https://orcid.org/0000-0002-6179-3329 (Інноваційна педагогіка. - 2023. - Вип. 56, т. 2. - С. 128-133, 2023)
Вивчено сучасний стан формування професійної компетентності майбутніх слідчих в умовах закладу вищої освіти зі специфічними умовами навчання. Виокремлено внутрішні (біологічні та психологічні), зовнішні (соціальні) чинники, які впливають на процес формування професійної компетентності майбутніх слідчих. Обґрунтовано необхідність нормативно-правового регулювання фахової підготовки слідчих, що є гарантією якості підготовки та дотримання їх прав та свобод при здійсненні професійної діяльності. Проаналізовано деякі сучасні нормативно-правові акти, які регламентують підготовку поліцейських.

The article is devoted to studying the current state of formation of professional competence of the future. The article contains separate internal (biological and psychological), external (social) factors that influence the process of forming the professional competence of future investigators. The necessity of normative-legal regulation of professional preparation of investigators is justified, which is a guarantee of quality of preparation and observance of their rights and freedoms during professional activity. Some modern legal acts regulating the preparation of police are analyzed. Specific features of professional preparation of future investigators: Combination of physical, intellectual and moral development of personality of future police officers; orientation of cadets on observance of norms of morality and taking into account requirements of professional ethics and deontology; training with enhanced military training, priority of discipline and special internal order; necessity of forming deep psychological and communicative knowledge. These features make it necessary to take into account them when introducing a three-level model of police training. The conditions that influence the effectiveness of the formation of professional competence of future investigators are defined: The process of psychological adaptation of cadets to specific, military conditions of study and support of their "entry" into the profession of the investigator; the organization of educational process and educational and methodical support of training in higher education institutions with specific conditions of study. When considering the first condition, the content of three stages of adaptation of cadets both to study in the НЕІ and to the future professional activity of the investigator is analyzed in detail. The problem issues of each stage are highlighted. Consideration of the second condition included analysis of educational and methodical support, theoretical and practical training of cadets in the context of formation of their professional competence. On the basis of the analysis, it was determined that training of personnel for investigation units of the National Police of Ukraine requires the construction and improvement of the educational process taking into account the provisions of the competent approach, which will help to improve the quality of investigative preparation.

Изучено современное состояние формирования профессиональной компетентности будущих следователей в условиях заведения высшего образования со специфическими условиями обучения. Выделены внутренние (биологические и психологические), внешние (социальные) факторы, влияющие на процесс формирования профессиональной компетентности будущих следователей. Обоснована необходимость нормативно правового регулирования профессиональной подготовки следователей, что является гарантией качества подготовки и соблюдения их прав и свобод при осуществлении профессиональной деятельности. Проанализированы некоторые современные нормативно-правовые акты, регламентирующие подготовку полицейских.
Analysis of the state of formation of professional competence of future investigators in HEI with specific education conditions
Скляр, О. С. Аналіз стану формування професійної компетентності майбутніх слідчих у ЗВО зі специфічними умовами навчання / Скляр О. С. // Інноваційна педагогіка. - 2023. - Вип. 56, т. 2. - С. 128-133. - DOI: https://doi.org/10.32782/2663- 6085/2023/56.2.28.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; заклади вищої освіти зі специфічними умовами навчання; institutions of higher education with specific study conditions; заведения высшего образования со специфическими условиями обучения; професійна компетентність; professional competence; профессиональная компетентность; професійна підготовка; professional training; профессиональная подготовка; освітній процес; educational process; образовательный процесс; майбутні слідчі; future investigators; будущие следователи